The Effect of Different Feed Types and Combinations on the Growth and Survival Rate Larvae on Manfish (Pterophyllum scalare) - Harisman Harisman; Sukendi Sukendi; Nur Asiah (Jurnal Akuakultur SEBATIN, 2021)
This Study aims to determine the type of feed that support growth and high survival for manfish. The research was carried out for 42 days (6 Weeks), at fish breeding and breeding laboratory (PPI) Department of Aquaculture. The method used in this study is the experimental method that uses one-factor Completely Randomized Design (CRD) consisting of six treatments with three replications. The treatment applied in this study is AR6 (Artemia sp. 6 weeks), KA6 (Water fleas 6 weeks), T6 (Tubifex sp. 6 weeks), AR3T3 (Artemia sp. 3 weeks, Tubifex sp. 3 weeks), KA3T3 (Water fleas 3 weeks, Tubifex sp. 3 weeks), and AR2KA2T2 (Artemia sp. 2 weeks, Water fleas 2weeks, Tubifex sp. 2 weeks). The result showed that the best treatment of types and their different food combination was found in T6 treatment (Tubifex sp. 6 weeks) produces absolute weight growth of 2,67 grams, growth of absolute length of 3,74 cm, specific growth rate of 13,05%, while the best survival rate found in the AR3T3 treatment (Artemia sp. 3 minggu, Tubifex sp. 3 minggu) is 85,67%. Water quality during the study was temperature ranging from 25-27,50C, pH ranged from 5,0-6,1 and DO was 5,0-6,7.